(untitled) (2014)
The aim of this article is to estimate the volatile organic compound (VOC) concentration in the air inside a composting pile based on their concentration in the compost and applying gas-liquid-solid equilibrium calculations. Gaseous and solid samples from a composting process were taken, and it has been proven that analysis of the solid samples permitted the determination of a larger number of VOCs (in a 40:1 ratio). Of all the VOCs found, monoaromatic hydrocarbons represent a higher risk to health because of their concentrations and persistence. Concentration of these compounds in the air inside the pile was estimated by phase equilibrium calculations, and establishing the hazard ratio leads to results very similar to those obtained in gas-sample-based studies. These findings confirm the existence of a health risk for compost facility workers through exposure to xylenes. © Copyright 2014, Mary Ann Liebert, Inc. 2014.